Epstein-Barr virus in gastric carcinoma. - Tokunaga, M. (1993)
Epstein-Barr virus (EBV) is known to be related to lymphoid tumors and some types of epithelial tumors, including lymphoepithelioma-like gastric carcinoma with marked lymphocytic stroma. In this study, prevalence of EBV involvement in gastric cancer, and characteristics of tumors with such involvement, were investigated by EBV-encoded RNA 1 in situ hybridization applied to paraffin sections, including the tumor and adjacent gastric tissue, from 999 gastric carcinomas observed in 970 consecutive cases from a large Japanese hospital. EBV involvement occurred in 6.9 percent of lesions, a significantly lower proportion than has been observed in a North American series. Involvement was significantly more frequent among males, in tumors in the upper part of the stomach, and in adenocarcinomas of the moderately differentiated tubular and poorly differentiated solid or medullary types. Almost all carcinomas with marked lymphoid stroma were EBV-positive. Positive lesions were characterized by the presence of uniform hybridized signals in almost all carcinoma cells and by their absence from adjacent non-neoplastic tissue.